Analisis Pengelolaan dan Peran Badan Usaha Milik Desa (Bumdes) Guna Peningkatan Perekonomian Masyarakat Desa Ditinjau Dari Perda Nomor 15 Tahun 2019 Mengenai Pembentukan dan Pengelolaan Badan Usaha Milik Desa: Studi Kasus pada Desa Jogosatru Kecamatan Sukodono Kabupaten Sidoarjo - Lisrotul Munawaroh; Maulidah Narastri (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to find out: (1) The implementation of the BUMDES program in improving the economy when viewed from regional regulation number 15 of 2019 in Jogosatru Village, Sukodono District, Sidoarjo Regency. (2) Knowing the role of BUMDES in improving the economy when viewed from regional regulation number 15 of 2019 in Jogosatru Village, Sukodono District, Sidoarjo Regency. The research method used is a case study with qualitative methods. The informants in this research were the village head, village secretary, village treasurer, Bumdes administrators, and representatives of the general Bumdes community. The research results show that the Jogosatru Village-Owned Enterprise (Bumdes) has succeeded in having an impact on improving the village community's economy through renting shops for business and opening job vacancies for business actors and increasing the PAD of Jogosatru village.